Le temps des morts-vivants : formes sérielles et potentiel critique des séries télévisées zombies - Clémentine Hougue (ReS Futurae, 2022)
This article examines the links between serial form and critical content in series featuring a zombie apocalypse. It proposes to analyze the American series The Walking Dead (AMC, 2010-auj.), based on the eponymous comic book, as well as its two spin-offs (Fear The Walking Dead, AMC, 2015-2021 and The Walking Dead : World Beyond, AMC, 2020), but also Z Nation (Syfy, 2014-2018) and its spin-off Black Summer (Netflix, 2019-2021), and the British miniseries Dead Set (E4, 2008). If George Romero brought zombies into the modern era, it is because he gave them a deeply political dimension, reflecting the fragile areas of contemporary Western civilization. But what about television series ? If they deal with the same theme - the survival of a group in a world suddenly invaded by the undead -, they do not hold the same discourse. The article thus aims to shed light on the way in which the context of production and broadcasting, and consequently the form and duration of these television series, substantially inform their critical content : after having analyzed the formal aspects of these television objects, it will be a question of defining the image of the « time of the end » that they constitute, by looking at the representation of the undead or of the survivors who face them.